Imidazole Derivative Cyclotriphosphazene-Based PLA/PEG Composite Films: Antibacterial Properties against Escherichia coli and Staphylococcus aureus - Demir, Irem; Seker, Gamze; Aysan, Arzu; Doganci, Merve Dandan; Davarci, Derya; Doganci, Erdinc (Amer Chemical Soc, 2025)
In this study, antimicrobial poly(lactic acid)/poly(ethylene glycol) (PLA/PEG) biofilms containing imidazole derivative cyclotriphosphazene compounds were prepared by using the solvent casting method. The mechanical, thermal, and biologically active properties of the obtained films were investigated. Biofilms were formed by adding the synthesized fully substituted methylimidazole and benzimidazole cyclotriphosphazene compounds (MCp and BCp) to the PLA/PEG mixture as additives at different rates. Tensile tests were performed on these films to examine their mechanical properties, including Young's modulus, elongation at break, and yield strength. It was observed that the mechanical properties of the films were slightly negatively affected by the addition of additives to the PLA/PEG films. When thermal stability analyses were examined, it was determined that the addition of the additives increased slightly, although not significantly. Antimicrobial tests were performed using Gram-negative Escherichia coli ATCC 53323 and Gram-positive Staphylococcus aureus ATCC 29213 bacterial strains for MCp and BCp and PLA/PEG composite films MCp and BCp, and PLA/PEG composite films containing these compounds. It was observed that MCp was much more effective than BCp in inhibiting the growth of Gram-positive and Gram-negative bacteria. Additionally, the PLA/PEG/MCp and PLA/PEG/BCp films had antibiofilm activity.